Ethical Challenges Faced by Social Work Trainee During Fieldwork Practice: Students’ Perspectives (Scholars' Journal, 2023)
Fieldwork practice is included and explained in social work education to develop and expand the social work profession. The most important aspect of the fieldwork practice for producing competent, effective, and ethical social workers is fieldwork discipline. The main objective of this study is to seek the ethical challenges for social work students in fieldwork practice the social work discipline in the context of Nepal. The theoretical portion of social work discipline is instructing in the classroom, and field-based practice combines the academic and practical components. The cornerstone of social work education is the fieldwork practicum; it currently faces various ethical challenges, including relying on different methodologies, methods, and tactics. For the study, descriptive qualitative research design was used, and secondary sources of data like journal articles, books, and reports were used in the research. Content analysis was used to draw the themes and results, primary theme investigated the ethical challenges faced by the fieldwork practice social work education in Nepal. To discuss the findings, content analysis on the themes was employed. By applying a relational ethics framework, the research can comprehensively investigate the moral dilemmas that social work candidates confront, considering the impact of relationships and contextual elements on moral judgment. This perspective offers a solid framework for examining and resolving ethical issues in fieldwork practice, consistent with the social work profession’s emphasis on the value of relationships.